The use of healthcare simulation to identify and address latent safety threats: a scoping review - Lounsbury, Olivia; Tomlinson, Ashley; Wakeling, Judy; Bowie, Paul; Higham, Helen (Frontiers in Health Services, 2025)
BackgroundSimulation is a well-established tool for clinical education and has been used to uncover latent safety threats (LSTs) in healthcare settings. However, the extent to which systems theory underpins efforts to detect and mitigate LSTs remains unclear.ObjectiveThis scoping review explores how healthcare simulations have been used to identify and address LSTs, with particular attention to the visibility and application of systems theory in study design, implementation, and analysis.MethodsUsing PRISMA-ScR, we systematically reviewed studies from 2014 to 2024 across MEDLINE, EMBASE, and grey literature sources. Studies were included if simulation was used with the primary aim of identifying LSTs. Data extraction focused on definitions of LSTs, approaches used to identify and analyse LSTs, response strategies, and the visibility of systems theory.ResultsSixty-six studies met inclusion criteria. Most (74.2%) used the term “latent safety threat,” though definitions varied. Many studies lacked explicit detail on how LSTs were identified (33.3%) or analysed (41.8%). Systems theory was applied with varying visibility: 36.4% showed unclear or no visibility, 43.9% showed partial visibility, and 19.7% showed full visibility. While 80.3% described actions to address LSTs, approaches ranged from one-off fixes to structured quality improvement strategies. Case studies illustrate best practices and opportunities for improvement in theoretical transparency.ConclusionsSimulation is a valuable method for identifying LSTs, but inconsistent application of systems theory and variable methodological transparency limit learning and generalisability. Future research should make theoretical underpinnings explicit, define terminology clearly, and align simulation design with both educational and organisational improvement goals.